2022
DOI: 10.3390/antibiotics11060808
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Self-Medication Practices for Prevention and Treatment of COVID-19: A Systematic Review

Abstract: It has been suggested that the COVID-19 pandemic led to an increase in self-medication practices across the world. Yet, there is no up-to-date synthesized evidence on the prevalence of self-medication that is attributable to the pandemic. This study aimed to conduct a systematic literature review on the prevalence and correlates of self-medication for the prevention and treatment of COVID-19 globally. The review was registered with the PROSPERO database. Searches were conducted following PRISMA guidelines, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
(85 reference statements)
1
27
0
1
Order By: Relevance
“…This study, which was conducted to estimate the cumulative prevalence of self-medication in the COVID-19 pandemic, showed that nearly half of the people have self-medicated. The results of a previous meta-analysis conducted on 14 relevant studies published between April 1, 2020, and March 31, 2022, showed that the pooled prevalence of self-medication was 44.9% ( 65 ). In addition to updating that study, we reported the results of 56 eligible studies by continent, target population, and time of data collection in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This study, which was conducted to estimate the cumulative prevalence of self-medication in the COVID-19 pandemic, showed that nearly half of the people have self-medicated. The results of a previous meta-analysis conducted on 14 relevant studies published between April 1, 2020, and March 31, 2022, showed that the pooled prevalence of self-medication was 44.9% ( 65 ). In addition to updating that study, we reported the results of 56 eligible studies by continent, target population, and time of data collection in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that a lot of people used dietary supplements and over-the counter drugs as self-medication for the prevention and treatment of COVID-19, and a systematic review was conducted [ 45 ]. This systematic review included 14 studies from 14 countries (Japan was not included), and the prevalence of self-medication for the prevention of COVID-19 was 44.9% (from 3.9% to 96.2% among studies).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there has been a surge in self-medication activities since the COVID-19 pandemic because of the societal perception of risk and the urge to accomplish something for preventative and curative reasons [ 54 , 55 , 56 ]. A recent systematic review revealed that the prevalence of COVID-19-related self-medication was 44.9%, and 79% of them were antibiotics [ 57 ]. This finding implies that the COVID-19 pandemic may increase the risk of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%